2015
DOI: 10.3390/magnetochemistry1010003
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 4-Hydroxy-2,6-di(pyrazol-1-yl)pyridine, and the Spin State Behaviour of Its Iron(II) Complex Salts

Abstract: 1 and 3), or in a mixed high:low spin state population at 150 K (2). Bulk samples of 1 and 2 obtained from methanol/diethyl ether contain a second, minor crystal phase that exhibits an abrupt spin-transition near 200 K. Recrystallisation of 1 and 2 from nitromethane/diethyl ether affords powder samples that are highly enriched in this spin-transition phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…In all cases, the signals of their terpy ligands are more paramagnetically shifted than those in the homoleptic complexes [Co­( L′ ) 2 ]­(ClO 4 ) 2 (or previously reported [Co­( L′ ) 2 ]­(OTf) 2 ), thus hinting on a larger population of the HS state as compared to the latter, which undergo an SCO in their pure solutions in acetonitrile-d 3 . The chemical shifts observed at room temperature for the 3-bpp ligands in the two types of cobalt­(II) complexes, of which the homoleptic compounds are always HS, ,,,,,, are inconclusive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all cases, the signals of their terpy ligands are more paramagnetically shifted than those in the homoleptic complexes [Co­( L′ ) 2 ]­(ClO 4 ) 2 (or previously reported [Co­( L′ ) 2 ]­(OTf) 2 ), thus hinting on a larger population of the HS state as compared to the latter, which undergo an SCO in their pure solutions in acetonitrile-d 3 . The chemical shifts observed at room temperature for the 3-bpp ligands in the two types of cobalt­(II) complexes, of which the homoleptic compounds are always HS, ,,,,,, are inconclusive.…”
Section: Resultsmentioning
confidence: 99%
“…In a search for SCO-active cobalt­(II) complexes of 3-bpp that are otherwise HS, ,,,,,, we attempted combining them with terpy coligands known to provide an appropriate ligand field for an SCO of the cobalt­(II) ion to occur. By mixing three previously synthesized 3-bpp ( L1 , L2 , and L3 ; Scheme ) ,,,, and two available terpy ( L1′ and L2′ ; Scheme ) ligands in a 1:1 ratio with a cobalt­(II) salt in an NMR tube, six new heteroleptic cobalt­(II) complexes were obtained in situ (Scheme ) together with five earlier reported homoleptic compounds , –the side products of the statistical synthesis–and they were screened for a possible SCO behavior by the NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the use of BF 4´a s the counterion results into a full SCO transition with a small hysteresis loop [23], whereas the use of ClO 4´r esults in the SCO molecules being kinetically trapped in its HS state [19,24]. Alternatively, modifications of the 1-bpp unit have been recently reported, obtaining (among others [25,26] (5) [27]. Even though the structure of the ligands is similar (see Scheme 1), their SCO properties are remarkably different, with transition temperatures of ca.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular complex [Fe(L1) 2 ]¨2ClO 4 , 1, (L1 = 2,6-bis{3-methylpyrazol-1-yl}pyrazine) is closely related to the family of spin crossover (SCO) active [Fe(bpp) 2 ] 2+ (bpp = 2,6-di{pyrazol-1-yl}pyridine) systems [10]. A previous SQUID magnetometry study of 1 revealed an unusual transition curve, consisting of two steps, separated not by a plateau as is often the case in stepped SCO materials [11], but rather by a change in gradient from an abrupt initial step (on cooling) followed by a much more gradual second step [12], as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%